Continuously Tunable Ion Rectification and Conductance in Submicrochannels Stemming from Thermoresponsive Polymer Self‐Assembly. (1st August 2019) - Wu, Yafeng; Yang, Guang; Lin, Mingchang; Kong, Xiangyu; Mi, Li; Liu, Songqin; Chen, Guosong; Tian, Ye; Jiang, Lei
Abstract: A biomimetic conical submicrochannel (tip side ca. 400 nm) with functions of continuously tunable ion rectification and conductance based on thermoresponsive polymer layer‐by‐layer (LbL) self‐assembly is presented. These self‐assembled polymers with different layers exhibited a capability to regulate the effective channel diameter, and different ion rectifications/conductance were achieved. By controlling temperature, the conformation and wettability of the assembled polymers were reversibly transformed, thus the ion rectification/conductance could be further adjusted subtly. Owing to the synergistic effect, the ion conductance could be tuned over a wide range spanning three orders of magnitude. Moreover, the proposed system can be applied for on‐demand on‐off molecule delivery, which was important for disease therapy. This study opens a new door for regulating channel size according to actual demand and sensing big targets with different size with one channel. Abstract : Ein biomimetischer Sub‐Mikrokanal (ca. 400 nm), basierend auf Schicht‐für‐Schicht‐Selbstassemblierung thermoresponsiver Polymere, weist kontinuierlich abstimmbare Ionengleichrichtung und ‐leitfähigkeit auf. Die Ionenleitfähigkeit kann dabei über einen weiten Bereich, der drei Größenordnungen umfasst, variiert werden.